How adverse and benevolent childhood experiences influence depression and suicidal ideation in Chinese undergraduates: a latent class analysis - Jie Tang; Jingjing Wang; Yifei Pei; Shiferaw Blen Dereje; Qian Chen; Na Yan; Yunjiao Luo; Yuhao Wang; Wei Wang (Komiyama Printing Co. Ltd, 2023)
Background: There has been minimal research on the role of benevolent childhood experiences (BCEs) and how such events may offer protection from the insidious effects of adverse childhood experiences (ACEs) or later in life. Objectives: This research aims to learn how BCEs and ACEs interact to affect adolescents' psychological distress. Methods: Cross-sectional survey was conducted in three cities (Xuzhou, Nanjing, and Wuhan) in China from March 2021 to May 2021. Latent class analysis (LCA) was used to classify the patterns of ACEs and BCEs. We adopted hierarchical multivariable regression to examine the influences of ACEs and BCEs on depression and suicidal ideation. Results: To explore the relationship between childhood experience and suicidal ideation and depression, LCA revealed three patterns of ACEs: (1) emotional abuse (10.57%); (2) high ACEs (0.55%); and (3) low ACEs classes (88.88%). Adolescents with emotional abuse (depression: OR = 3.82, 95%CI = 2.80-5.22, P < 0.001; suicidal ideation: OR = 5.766, 95%CI = 3.97-8.38, P < 0.001) and high ACEs class (suicidal ideation: OR = 5.93, 95%CI = 1.19-29.66, P < 0.05) had an increased risk of psychological distress (reference: low ACEs). LCA revealed four patterns of BCEs: (1) relationship support (14.54%); (2) low BCEs (4.85%); (3) high BCEs (55.34%); and (4) high quality of life classes (25.28%). Adolescents with a high quality of life (depression: OR = 0.09, 95%CI = 0.05-0.16, P < 0.001; suicidal ideation: OR = 0.22, 95%CI = 0.12-0.40, P < 0.001) and high BCEs (depression: OR = 0.05, 95%CI = 0.03-0.09, P < 0.001; suicidal ideation: OR = 0.15, 95%CI = 0.09-0.26, P < 0.001) protected the mental health of adolescents (reference: low BCEs). Conclusions: High ACEs and emotional abuse classes were significantly associated with poorer mental health symptoms, including suicidal ideation and depression. In contrast, high BCEs and high quality of life classes were associated with better mental health. These findings point out that it is more necessary to identify and support victims of ACEs, and it is urgent to increase BCEs in early childhood.